Winn-Dixie Stores in 2005 (B) : cleanup on aisle 11 - Shein, James; Meagher, Evan (London : SAGE Publications Ltd, 2017)
Grocery store chain Winn-Dixie had rapidly expanded in an effort to become a national retailer, and by 1999 it had more than 1,000 stores. The company began manufacturing its own products, reasoning that by owning more of the supply chain, it could offer the customer less expensive options. With its new geographic focus and manufacturing facilities, Winn-Dixie attempted to secure a position as a low-cost provider with a national presence. Instead of improving the companys position in the market, however, this strategy crippled both the short- and long-term prospects for Winn-Dixie. The company paid a high premium to expand and increased its leverage without ever realizing the purposed synergies. In fact, there were dis-economies of scale because the distribution, marketing, and administrative costs had risen along with the increased revenue. The expansion and inefficient manufacturing added complexity to its distribution network and with a greater debt load and less cash, the company was unable to reposition itself in the market when its low-cost provider strategy failed. Not only was the company unable to pursue other opportunities but it also did not have the cash to properly maintain many of its existing stores, which quickly became run down. Winn-Dixie was stuck as a general grocer with few options at a time when the industry was rapidly evolving. Following faulty strategies of expansion, supply chain changes, and increased debt, Winn-Dixie declared bankruptcy. Students will take the view that Paul "Flip" Huffard, lead consultant from Blackstone LP, had in determining the valuation and new capital structure of the company. These decisions would be critical, as they affected what each creditor class would receive and whether Winn-Dixie could emerge from bankruptcy.
Originally published: Shein, J., & Meagher, E. (2008). Winn-Dixie stores in 2005 (B): Cleanup on aisle 11. 5-408-751(B). Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Winn-Dixie Stores -- Case studies; Grocery trade -- United States -- Case studies; Chain stores -- United States -- Case studies